PENGARUH CORPORATE SOCIAL RESPONSIBILITY (CSR) TERHADAP FINANCIAL PERFORMANCE, FINANCIAL STABILITY, DAN FINANCIAL INCLUSION PADA PERUSAHAAN PERBANKAN (Studi pada Perusahaan Perbankan yang Terdaftar di Bursa Efek Indonesia Periode 2016- 2020) - Amelia Sabela Cahyaningrum; Harjum Muharam (Faculty of Economics and Business Diponegoro University, 2023)
ABSTRACT This study aims to analyze the effect of corporate social responsibility on financial performance, financial stability, and financial inclusion of Indonesian banking companies for the 2016-2020 period. Financial performance is measured using return on assets (ROA), return on equity (ROE), earnings per share (EPS), and net profit margin (NPM). Financial stability is measured using Z-Score, and financial inclusion is measured using the number of bank branches (NOBB) and the number of bank ATMs (NOBA) per 100,000 adult population. The independent variable used in this study is corporate social responsibility (CSR) and is followed by control variables consisting of leverage (LEV), tangibility, company age (AGE), and company size (SIZE). The samples used in this study were collected from 33 banking companies listed on the Indonesia Stock Exchange (IDX) with complete data needed to calculate the variables in the study in the 2016-2020 period. Samples were taken using purposive sampling method. Research data obtained from Bloomberg and the company's annual financial statements. The data was processed using Ordinary Least Square (OLS) regression analysis and Hypothesis Test with the help of the SPSS version 26 and Eviews 10 application programs. The results show that CSR, tangibility and firm size have a significant influence on all three factors. However, high firm age has no impact on the financial stability of banks, while high leverage levels reduce financial inclusion